Study of cholecystectomy specimens over a period of one year in tertiary care centre - Bharathi, I. Vijaya; Devi, P. Urmila; Lakshmi, A. Bhagya (International Journal of Research in Medical Sciences, 2017)
Background: Gall bladder is among the most common surgically resected organs with various neoplastic and non-neoplastic lesions. Chronic chocystitis is the most commonly encountered lesion in India and worldwide and 78-90% are associated with calculi. Gall bladder cancer constitutes 0.5% to 1.09% including both suspected and incidental diagnosis. The objective of present study was to evaluate the various lesions of Gall bladder and the importance of grossing and histopathological examination of every cholecystectomy specimen in order to diagnose the incidental gall bladder cancer (IGBC). Methods: A Retrospective study of cholecystectomy specimens for a period of one year, May 2015 to June 2016 was carried out. 252 Cholecystectomy specimens were received and all of them subjected for histopathological examination and the sections stained with routine Hematoxylin and Eosin stain. Results: Commonest age group being 21-40years (41%) followed by 41-60years (40%). Gall bladder (GB) lesions are more common in females 175 (70%) and M:F ratio 1:2.2.Most commonest lesions were Chronic calculous cholecystitis constituting 155 cases (61%) followed by chronic cholecystitis 52 cases (21%). Cholelithiasis was associated with both Acute and Chronic Cholecytitis constituting 67%. Acute calculous cholecystits constitute 13 cases (5%) and Acute cholecystitis constitutes 10 cases (4%). In Congenital anomalies, 3 cases (1.2%) of Biliary atresia and 4 cases (1.2%) of choledochal cyst were diagnosed. 4 cases (1.6%) of Gall bladder carcinoma was diagnosed. Among these 3 cases were incidental gall bladder carcinoma (IGBC). Conclusions: cholecystectomy specimens should be subjected for histopathological examination to study various lesions of GB and to detect unsuspected incidental gall bladder cancer as cholecystectomy itself is the treatment for gall bladder cancer and also other lesions of GB associated with cholelithiasis.